2008
DOI: 10.1002/jor.20763
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of different intraarticular tissues to the acute phase elevation of synovial fluid MMP‐2 following rat ACL rupture

Abstract: Inflammation and accumulation of matrix metalloproteinases (MMPs) in synovial fluids may be involved in the poor healing ability of the anterior cruciate ligament (ACL) after injury. With a rat ACL rotating injury model, we found that levels of IL-1beta, IL-6, and TNF-alpha were significantly higher in synovial fluids after ACL injury. MMP-2 activity and global MMP activity in synovial fluids also increased significantly in a time-dependent manner. Ex vivo studies showed that all tissues contributed to the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…30 Previously, another in vivo model study from our lab also revealed that intra-articular tissue have contributed to the accumulation of MMP-2 production and its elevated proteolytic activity in joint fluid after mechanical injury. 11 Since MMPs are largely involved in the breakdown of ECM in normal physiological processes as well as disease processes, this may suggest one mechanism by which the knee joint tissue are difficult to repair. The accumulation of MMP-2 in the joint fluid after injury might disrupt the delicate balance of removing damaged matrix components with the deposition of newly synthesized materials.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…30 Previously, another in vivo model study from our lab also revealed that intra-articular tissue have contributed to the accumulation of MMP-2 production and its elevated proteolytic activity in joint fluid after mechanical injury. 11 Since MMPs are largely involved in the breakdown of ECM in normal physiological processes as well as disease processes, this may suggest one mechanism by which the knee joint tissue are difficult to repair. The accumulation of MMP-2 in the joint fluid after injury might disrupt the delicate balance of removing damaged matrix components with the deposition of newly synthesized materials.…”
Section: Discussionmentioning
confidence: 99%
“…18 Earlier studies have shown that ACL fibroblast repair directly relates to MMP-2 production. 11 Previously, we have reported increased amount of TNF-a, IL-1b, and IL-6 in the joint fluid during the acute inflammatory phase after ACL injury. 11 These cytokines are also considered important chemical mediators in the acute inflammatory phase of wound healing.…”
mentioning
confidence: 90%
See 3 more Smart Citations